1995
DOI: 10.1183/09031936.95.08071130
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory muscle strength and endurance in myasthenia gravis

Abstract: V Ve en nt ti il la at to or ry y m mu us sc cl le e s st tr re en ng gt th h a an nd d e en nd du ur ra an nc ce e i in n m my ya as st th he en ni ia a g gr ra av vi is s We studied 17 patients with myasthenia gravis (four with ocular involvement alone and 13 with varying degrees of generalized myasthenia gravis). Spirometry, ventilatory muscle strength (maximum inspiratory and expiratory pressures (MIP and MEP)) and endurance (2 min incremental threshold loading test) were measured before and 20 min after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 15 publications
2
25
1
6
Order By: Relevance
“…subjects and 27 subjects (100%) lower P Imax values, so determining high values of P Emax /P Imax . Our results are apparently in partial disagreement with those of Weiner et al 17 and Keenan et al, 18 who studied subjects with severe and moderate generalized MG, and found that both P Emax and P Imax were lower than normal. However, our group of MG subjects included those with only mild/moderate, and not severe, generalized MG.…”
Section: Discussioncontrasting
confidence: 57%
“…subjects and 27 subjects (100%) lower P Imax values, so determining high values of P Emax /P Imax . Our results are apparently in partial disagreement with those of Weiner et al 17 and Keenan et al, 18 who studied subjects with severe and moderate generalized MG, and found that both P Emax and P Imax were lower than normal. However, our group of MG subjects included those with only mild/moderate, and not severe, generalized MG.…”
Section: Discussioncontrasting
confidence: 57%
“…Indeed, in our series as well as in the literature [3], most MG patients presented with PFT values in the range of normal, and MG-induced restrictive ventilatory patterns or low vital capacity were rarely observed. Surprisingly, in our study, we found that the first cause of dyspnea not related to MG was asthma (14% of our 63 patients), followed by obesity and tobacco-induced PFT abnormalities, while in the general adult population, tobacco-induced chronic obstructive pulmonary disease prevalence (10%) and obesity prevalence (16%) are higher than asthma prevalence (6%) [2].…”
Section: Discussionmentioning
confidence: 80%
“…Bu nedenlerin başlıcaları, "amyotrophic lateral sclerosis (ALS)", myastenia gravis, polymyozitis, Guillain-Barré sendromu gibi nöromusküler hastalıklar ya da kalp yetmezliği, tirotoksikoz, malnütrisyon, yoğun bakım sonrası sendromu gibi durumlardır (35,51,52,(57)(58)(59)(60).…”
Section: Kli̇ni̇k Kullanimunclassified